Projeto de mecanismo de transmissão para uma roda sem a utilização de raios - Sutilli, Jofre (2014)
The spoked wheel, usually used on bicycles, is one of the most important mechanical manufacturing products produced by man. The wheel rim is joined to the hub through the spokes, when it is well assembled, provides a good resistance to the wheel. A new issue is the transmission mechanism for a wheel without spokes. It was designed and built a prototype of wheel without spokes using a toothed belt and pulley, employing a planetary gear system. The wheel without spokes mechanism proved to be feasible in the constructive sense. Although the mechanism can be constructed of lightweight materials, friction qualitatively, showed significant with regard to efficiency rolling.